2014
DOI: 10.1155/2014/486423
|View full text |Cite
|
Sign up to set email alerts
|

CFD Method for Predicting Annular Pressure Losses and Cuttings Concentration in Eccentric Horizontal Wells

Abstract: In oil and gas drilling operations, predictions of pressure losses and cuttings concentration in the annulus are very complex due to the combination of interacting drilling parameters. Past studies have proposed many empirical correlations to estimate pressure losses and cuttings concentration. However, these developed correlations are limited to their experimental data range and setup, and hence, they cannot be applicable to all cases. CFD methods have the advantages of handling complex multiphase flow proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…Similar pressure drop predictions have been performed by Ofei et al (2014) using the experiments of Han et al (2010) and Osgouei (2010). The Eulerian-Eulerian model implemented in their work yielded a mean error of less than 5%.…”
Section: Cfd Model Validationsupporting
confidence: 73%
See 2 more Smart Citations
“…Similar pressure drop predictions have been performed by Ofei et al (2014) using the experiments of Han et al (2010) and Osgouei (2010). The Eulerian-Eulerian model implemented in their work yielded a mean error of less than 5%.…”
Section: Cfd Model Validationsupporting
confidence: 73%
“…It was also shown that fluid flow rate, hole inclination angle and ROP have a major impact on the transport efficiency. Ofei et al (2014) implemented the Eulerian-Eulerian multiphase model to predict cuttings concentration and pressure losses at different diameter ratios in eccentric horizontal annuli. According to their results, drilling mud had superior transport capabilities compared to water at low diameter ratios; however, the performance of both fluids can be similar at a high diameter ratio of 0.9.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In the study of Ofei et al [3,4] influence of drill pipe rotation was numerically investigated. In article Mokhtari et al [5] investigated influence of yield stress.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies [17][18][19][20][21][22][23][24][25][26][27][28] have adopted CFD techniques to model solid-liquid flow in annular geometries with much accuracy. This is due to the many advantages CFD has over experimental setup and empirical correlations in handling complex multiphase flow problems with unlimited physical and operational conditions.…”
Section: Introductionmentioning
confidence: 99%